Analysis of Corrosion Rate With Addition of Pumps in Commercial Steel in Sea Water Media - Rini Selly; Ricky Andi Syahputra; Moondra Zubir; Lisnawaty Simatupang; Erpida Ompusunggu; Jesicca Aprilyani; Nopita Sitompul (Universitas Negeri Medan, 2020)
Corrosion or rusting is very common in metals is a decrease in the ability of a metal due to the environment or chemicals. Sea water is a corrosive environment for metals because it contains sodium chloride (NaCl), calcium sulfate (CaSO4), calcium carbonate (CaCO3), and dissolved oxygen (O2) which affect the corrosion process of the material. The presence of dissolved oxygen will cause the rate of corrosion in metals to increase with increasing oxygen content (O2), the solubility of oxygen in water is a function of pressure, temperature and chloride content. The process of corrosion is almost the same for all materials, especially in metals occurs slowly but surely, corrosion can cause a material to have a limited service life, where the material expected to be used for a long time turns out to have a shorter life span than the average usage life.